The geography of international portfolio flows, international CAPM and the role of monetary policy frameworks - Roberto A. De Santis (European Central Bank (ECB), 2006)
Using bilateral data on international equity and bond flows, we find that the prediction of the International Capital Asset Pricing Model is partially met and that global equity markets might be more integrated than global bond markets. Moreover, over the turbulent 1998-2001 period characterised by an equity bubble and the subsequent burst, we find evidence that investors preferred portfolio assets of countries where the central bank gave relative importance to money. As for EMU, once controlling for diversification benefits and the elimination of the exchange rate risk, we show that cross-border portfolio flows among euro area countries have increased due to the catalyst effect of EMU. Country's shares in the world market portfolio, home bias, initial degree of misallocation across countries, past returns, diversification benefits and EMU can explain 35-40% of the total variation in equity and bond asset flows.
Keywords: C13; C21; F37; G11; 330; Capital flows; EMU; home bias; monetary policy; Risk diversification; CAPM; Kapitalmobilität; Portfolio-Management; Währungsrisiko; Eurozone; Theorie; EU-Staaten